2021
DOI: 10.20944/preprints202111.0389.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emerging Fabrication Techniques for Engineering Extracellular Matrix Biomimetic Materials

Abstract: There is need to address the challenges of organ shortage, through development of tissues and organs with alternatives to those of the allograft-kind. This illustrates the quest behind novel biofabrication strategies such as 3D bio-printing, which is necessary to create artificial multi-cellular tissues/organs. Several findings have been reported in this review. First, the role of ECM components in tissue regenerative medicine is presented. Different ECM components such as collagen, gelatin, elastin, fibronect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…It also improves bone cell adhesion and migration due to Arg-Gly-Asp sequences [47]. Samadian et al demonstrated in vivo that gelatin can stimulate neo-bone formation, osteocytes in lacuna woven bone formation, and angiogenesis in the defect position [48]. The fact that gelatin is a polypeptide with a high molecular weight and derived from the thermal denaturation of collagen makes it not only less expensive than collagen but also easier to obtain from concentrated solutions and less immunogenic.…”
Section: Collagen and Gelatinmentioning
confidence: 99%
“…It also improves bone cell adhesion and migration due to Arg-Gly-Asp sequences [47]. Samadian et al demonstrated in vivo that gelatin can stimulate neo-bone formation, osteocytes in lacuna woven bone formation, and angiogenesis in the defect position [48]. The fact that gelatin is a polypeptide with a high molecular weight and derived from the thermal denaturation of collagen makes it not only less expensive than collagen but also easier to obtain from concentrated solutions and less immunogenic.…”
Section: Collagen and Gelatinmentioning
confidence: 99%